Regulation of Gene Expression Associated With the N6-Methyladenosine (m6A) Enzyme System and Its Significance in Cancer - Tian, Shuoran; Lai, Junzhong; Yu, Tingting; Li, Qiumei; Chen, Qi (Frontiers in Oncology, 2021)
N6-methyladenosine (m6A), an important RNA modification, is a reversible behavior catalyzed by methyltransferase complexes (m6A “writers”), demethylated transferases (m6A “erasers”), and binding proteins (m6A “readers”). It plays a vital regulatory role in biological functions, involving in a variety of physiological and pathological processes. The level of m6A will affect the RNA metabolism including the degradation of mRNA, and processing or translation of the modified RNA. Its abnormal changes will lead to disrupting the regulation of gene expression and promoting the occurrence of aberrant cell behavior. The abnormal expression of m6A enzyme system can be a crucial impact disturbing the abundance of m6A, thus affecting the expression of oncogenes or tumor suppressor genes in various types of cancer. In this review, we elucidate the special role of m6A “writers”, “erasers”, and “readers” in normal physiology, and how their altered expression affects the cell metabolism and promotes the occurrence of tumors. We also discuss the potential to target these enzymes for cancer diagnosis, prognosis, and the development of new therapies.